2001
DOI: 10.1016/s0005-2728(01)00169-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel scenario for the evolution of haem–copper oxygen reductases

Abstract: The increasing sequence information on oxygen reductases of the haem-copper superfamily, together with the available three-dimensional structures, allows a clear identification of their common, functionally important features. Taking into consideration both the overall amino acid sequences of the core subunits and key residues involved in proton transfer, a novel hypothesis for the molecular evolution of these enzymes is proposed. Three main families of oxygen reductases are identified on the basis of common f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
468
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(487 citation statements)
references
References 87 publications
17
468
2
Order By: Relevance
“…In Aand B-type COXs, on the other hand, positively charged groups from two conserved arginine residues locate at the equivalent position to the Ca ion (18)(19)(20)(21). It is therefore likely that NORs and C-type COX are closely related to one another and are evolutionary distinct from A-and B-type COXs, which is consistent with the view from the phylogenetic analysis (7,22).…”
Section: Structures Of Bacterial Nors: Structural Evidence For Evolutsupporting
confidence: 82%
See 1 more Smart Citation
“…In Aand B-type COXs, on the other hand, positively charged groups from two conserved arginine residues locate at the equivalent position to the Ca ion (18)(19)(20)(21). It is therefore likely that NORs and C-type COX are closely related to one another and are evolutionary distinct from A-and B-type COXs, which is consistent with the view from the phylogenetic analysis (7,22).…”
Section: Structures Of Bacterial Nors: Structural Evidence For Evolutsupporting
confidence: 82%
“…2H 2 O), shows sequence similarities to NOR (4,5). Phylogenetic analysis suggested that NOR and COX are classified as members of the heme-copper oxidase superfamily and share the same ancestor protein (5)(6)(7). NORs and some COXs have crossreactivity with respective substrate (8)(9)(10), further supporting the view that NOR is evolutionary related to COX.…”
Section: Introductionmentioning
confidence: 75%
“…Independent of these geological arguments, the history of oxidase enzymes places other constraints on the origins of aerobiosis (30,43,44). Although there is active debate on the phylogenetic history of oxidase enzymes, recent models (30,43,44) support an ancient origin, even before the evolution of oxygen-producing cyanobacteria (45). Without a cyanobacterial source, oxygen could have come from abiotic sources, such as the rainout and disproportionation (by catalase enzymes) of atmospherically produced H 2 O 2 at the Earth's surface.…”
Section: Resultsmentioning
confidence: 99%
“…The residues for the K channel of proton pumping are conserved in both oxidases (PoxC: Y257, S268, S328, K331; and PoxI: Y223, S234, S295, Y299). On the other hand, the residues necessary for the D channel of haem-copper oxidases are conserved in PoxC (N89, N107, D100, T165, F251, G252 and E255), but are not conserved in PoxI as for other known SoxB-type haem-copper oxidases like those of Sulfolobus acidocaldarius, Acidianus ambivalens, Thermus thermophilus and Geobacillus stearothermophilus (Riistama et al, 1996;Purschke et al, 1997;Keightley et al, 1995;Nikaido et al, 1998;Pereira et al, 2001 poxJ encodes a homologue of scoI of Saccharomyces cerevisiae that is widely conserved in eukarya, proteobacteria and Aquifex aeolicus (Chinenov, 2000). Alignment of ScoI-related proteins showed that PoxJ contained Cu(I)-binding residues (C84, C88 and H169) (Nittis et al, 2001).…”
Section: Putative Topologies Of Subunitsmentioning
confidence: 99%